Tradability of output, business cycles and asset prices - Tian, Mary (Journal of Financial Economics, 2018)
I examine the effect of a firm’s tradability, the proportion of output that is exported abroad, on its stock returns over business cycles from 1947–2015. Firms with higher tradability have more cyclical asset returns, even after controlling for the real exchange rate. Returns of a portfolio long on firms with the highest tradability and short on firms with the lowest tradability can predict changes in the real dollar exchange rate and trade volumes. The empirical patterns are consistent with the relative price adjustment of tradable and non-tradable goods to business cycles primarily driven by supply shocks.